2003
DOI: 10.1053/jlts.2003.50057
|View full text |Cite
|
Sign up to set email alerts
|

Late hepatic artery thrombosis after orthotopic liver transplantation

Abstract: Late hepatic artery thrombosis (HAT) is a rare complication after orthotopic liver transplantation (OLT), conventionally described as occurring more than 30 days after surgery. Only a few reports document its course. In a consecutive series of 634 OLTs (704 grafts), 11 patients (1.7%) had late HAT, diagnosed a median of 6 months (range, 1.8 to 79 months) after OLT. Clinical variables were compared with those of 415 patients without HAT who had a complete database and follow-up, including cytomegalovirus (CMV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
1
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(127 citation statements)
references
References 19 publications
4
115
1
7
Order By: Relevance
“…The available analyses 1,2,[4][5][6]12,13 are largely drawn from experiences of the early days of liver transplantation, and most fail to demonstrate clear risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The available analyses 1,2,[4][5][6]12,13 are largely drawn from experiences of the early days of liver transplantation, and most fail to demonstrate clear risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was reported that arterial anastomosis with operation microscope or loupe mangnification did not show any difference in incidence HAT [9,17,28,41] . Late HAT shows a lower incidence, ranging from 1% to 25% [38,42] . Torras et al [34] .…”
Section: Incidencementioning
confidence: 97%
“…The presentation may be insidious. Liver graft ischemia and liver failure are other classical insidious clinical outcomes revealing late HAT [17,27,28,36,38,42,43] .…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Probably children have more facilities to revascularize the liver through all the adhesions of the graft to the diaphragm, and other adjacent organs [10]. In adults, even in the late phase after transplantation, hepatic artery occlusion may induce severe biliary complications such as biliary necrosis, biliary leak or liver abscesses [11,12]. The range of clinical symptoms goes from acute liver failure and death to biliary anastomotic stenosis.…”
Section: Arterial Complicationsmentioning
confidence: 99%